The Effect of Using the Al-Hira’ Method and Guided Reading on the Ability to Read the Qur'an of Elementary Education Level Students - Ahfadh, Zuhri; Ritonga, Asnil Aidah; Ahkas, Akmal Walad (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to determine the effect of using the al-Hira' method and guided reading on the ability to read the Qur'an of elementary education level students. This study uses a quantitative approach with a quasi-experimental method and a one-group pretest-posttest research design. The population in this study amounted to 48 people. Sampling in this study was conducted using a cluster random sampling of 48 people, consisting of 24 people in class VII1 who were taught using the Al-Hira' method and 24 people in class VII2 who were taught using the guided reading method. The results of this study conclude that there is an influence of the Al-Hira' method and the guided reading method on the ability to read the Qur'an of the students of Madrasah Sanawiah (MS) Private Maura El-Mumtaz Binjai, where the results of hypothesis testing that have been carried out in the Al method class -Hira' and the guided reading method class used the t-test, so the results were tcount > ttable (4.553 > 2.069) which means Ha is accepted and H0 is rejected while the difference between the Al-Hira' method and the guided reading method can be seen from the average value pretest and posttest, where the average value of the posttest of the Al-Hira' method is higher than the average value of the posttest of the guided reading method, and the average value of the pretest of the Al-Hira' method is higher than the average value of the pretest of the guided reading method.